Hubungan Tingkat Depresi Dengan Faktor-Faktor Yang Mempengaruhi Pada Pasien Lansia Di Layanan Rawat Jalan Puskesmas Turi Lamongan - Anindita, Yustika Izziyatu; Prasetya, Era Catur; Levani, Yelvi (Journal of Islamic Medicine, 2022)
Background: Depression is a mental health disorder that could affect to geriatric. There are several factors that can affect depression such as age, gender, occupation, caregiver status, and chronic disease. Puskesmas as primary health facilities should be the first line for the community to get comprehensive health services both in terms of physical and mental health. Objective: This study aims to determine the description of depression in elderly patients in outpatient services at the Turi Lamongan Health Center, along with what factors influence it. Methods: This study is a descriptive analytic study with a cross sectional design, with 65 elderly patients in the outpatient health center as the subject. The data was collected by interviewing using the GDS (Geriatric Depression Scale) questionnaire, demographic data and secondary data from the Puskesmas Turi Lamongan medical records on February until March 2022. Data were analyzed using Chi-Square and Fisher's Exact tests using SPSS. Results: Depression level description: 61.5% normal, 36.9% mild, 1.5% moderate, 0% severe. There is a relationship between gender, caregiver status and metabolic disease with depression. There is no relationship between depression with age and gender. Conclusion: There is a relationship between the level of depression with several factors such as gender, caregiver status and metabolic disease in elderly patients in outpatient services at the Turi Lamongan Health CenterKeyword : Depression, Geriatry, Health care facilities, Factors Outpatient Clinic